Máquinas de somar estocásticas e conjuntos de Julia - Caprio, Danilo Antonio [UNESP] (2015)
In this work we define a stochastic adding machine associated to the Fibonacci baseand to a probabilities sequence (Pi) i>1. We obtain a Markov chain whose states are the set of nonnegative integers. We study probabilistic properties of this chain, such as transience and recurrence. We also prove that the spectrum associated to this Markov chain is connected to the filled Julia sets for a class of endomorphisms in C 2. Furthermore, we study topological and dynamical properties of a class of endomorphisms of C 2 (or R 2). Precisely, the considered maps are fn(x, y) = (x y + cn, x), where cn 2 C (or cn E R), for all n>0.